The Concept of Justice in the Perspective of Greece Philosophy and its Relevance to the Development of Modern Political Law - Wahyudi, Ade Arga; Marlian Arif Nasution; Paisal Rahmat (Journal of Law, Politic and Humanities, 2022)
The concept of justice will continue to develop in line with social developments. Justice in life is an important need for humans so that everyone can balance between demanding their rights and carrying out their obligations in an effort to achieve the truth. Thus, truth and duty must be harmonious and balanced in life. The development of legal thought has gone through a long journey from classical to modern times. The number of understandings that developed starting in the 20th century had an impact on increasingly rational legal learning. The law is just a collection of words when the law does not achieve justice. When the law does not recognize justice, then the law is meaningless. Legal formulation is the harmony between legal certainty and legal proportionality.